Pragmatic guide to Sass - Catlin, Hampton; Catlin, Michael Lintorn (Pragmatic programmers., 2011)
CSS is fundamental to the web, but it's a basic language and lacks many features. Sass is just like CSS, but with a whole lot of extra power so you can get more done, more quickly. Build better web pages today with Pragmatic Guide to Sass . These concise, easy-to-digest tips and techniques are the shortcuts experienced CSS developers need to start developing in Sass today.